A Case Study: Dispersionand Explosion Quantitative Risks Assessment in an Ammonia Plant - Abdurrohman Abdurrohman; Fatma Lestari (Jurnal Impresi Indonesia, 2025)
Ammonia is a highly toxic substance, and its dispersion in industrial settings presents significant risks to both personnel and surrounding communities. This study focuses on the risk assessment of ammonia gas dispersion and explosion scenarios in an ammonia plant. The research aims to evaluate the exposure risks associated with ammonia leaks, assess the effectiveness of mitigation measures, and provide safety recommendations. The study uses a semi-integrated 2D modeling approach for consequence modeling, with hazard identification and event tree analysis to calculate leak frequencies and potential final events. The exposure risk evaluation indicates that the entire target area is at risk of exposure to ammonia gas at concentrations above the threshold of 35 ppmv, due to high ammonia content in the process flow and operational pressures. Key findings suggest that the most at-risk areas include control rooms, workshop areas, and assembly points. To mitigate these risks, recommendations include engineering controls, improved toxic gas detection systems, and enhanced safety measures such as regular maintenance of equipment, double-door procedures, and personal protective equipment (PPE). The implications of this research stress the need for ongoing safety assessments and preventive strategies to reduce potential exposure risks in ammonia handling facilities.